2017
DOI: 10.1080/09546634.2016.1274365
|View full text |Cite
|
Sign up to set email alerts
|

Dermatologic radiotherapy in the treatment of extensive basal cell carcinomas: a retrospective study

Abstract: The treatment of extensive BCC is still a challenge and radiotherapy is one of the possible choices, preferred in the elderly, in relapsing cases, after incomplete excision, and in difficult localisations of the face. Radiotherapy might be included in sequential schedules of treatment to improve final results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
1
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 20 publications
1
18
1
4
Order By: Relevance
“…While surgical treatment is the gold standard of local BCC therapy, certain tumor features (size, infiltration of deep structures, sites associated with mutilating surgery), comorbidity, or patient preference may result in choosing a non‐surgical procedure. Multiple publications (case series, retrospective studies, reviews) have shown clinical control rates of 92 % to 99 % for smaller BCCs and 70 % to 90 % for high‐risk BCCs (large size, high‐risk sites, or recurrence) (follow‐up period between four months and ten years) for various types of radiation therapy (predominantly brachytherapy, but also electron and orthovoltage radiation therapy) . The only randomized study (n = 347) that compared surgery and radiation therapy (1 : 1 randomization) showed surgery to be significantly superior in terms of local disease control, with 99.3 % versus 92.5 % after 4 years (maximum follow‐up period) .…”
Section: Risk Stratificationmentioning
confidence: 99%
See 1 more Smart Citation
“…While surgical treatment is the gold standard of local BCC therapy, certain tumor features (size, infiltration of deep structures, sites associated with mutilating surgery), comorbidity, or patient preference may result in choosing a non‐surgical procedure. Multiple publications (case series, retrospective studies, reviews) have shown clinical control rates of 92 % to 99 % for smaller BCCs and 70 % to 90 % for high‐risk BCCs (large size, high‐risk sites, or recurrence) (follow‐up period between four months and ten years) for various types of radiation therapy (predominantly brachytherapy, but also electron and orthovoltage radiation therapy) . The only randomized study (n = 347) that compared surgery and radiation therapy (1 : 1 randomization) showed surgery to be significantly superior in terms of local disease control, with 99.3 % versus 92.5 % after 4 years (maximum follow‐up period) .…”
Section: Risk Stratificationmentioning
confidence: 99%
“…reported on a total of 1,300 tumors treated with low‐voltage (soft) X‐rays (94.9 % clinical tumor clearance with a mean follow‐up period of 77 months) . However, extreme caution is required for deeply infiltrating lesions as low‐voltage (soft) X‐rays in particular are disadvantageous in terms of tumor control due to their low depth of penetration and efficacy (beyond 5 mm tumor depth, there is < 90 % of the physical dose [energy of 50 kV], with exponential decrease towards deeper layers) . The total dose for normofractionated regimens (five fractions of 2 Gy each per week) should be at least 60 Gy; for larger lesions (> 2 cm horizontal diameter), the dose may be increased to 66 Gy.…”
Section: Risk Stratificationmentioning
confidence: 99%
“…Allerdings können bestimmte Tumormerkmale (Ausdehnung, Infiltration von tiefen Strukturen, Lokalisation an Stellen, die zu mutilierenden Operationen führen), Komorbidität oder auch Patientenpräferenz zur Wahl eines nichtoperativen Verfahrens führen. In multiplen Untersuchungen (Fallserien, retrospektiven Studien, Reviews) konnten klinische Kontrollraten von 92 % bis 99 % für kleinere BZK und 70 % bis 90 % für Hochrisiko‐BZK mit großer Ausdehnung, Risikolokalisation oder Rezidivsituationen zusammengetragen werden (Nachbeobachtungszeit zwischen 4 Monaten und 10 Jahren), wobei verschiedene Strahlentherapiemodalitäten zum Einsatz kamen (überwiegend Brachytherapie, zudem Elektronen, Orthovolt‐Bestrahlung) . Die einzige randomisierte Studie (n = 347), die zwischen Operation und Strahlentherapie verglichen hat (1 : 1‐Randomisierung), zeigt eine signifikante Überlegenheit der Operation bezüglich lokaler Kontrolle mit 99,3 % versus 92,5 % nach 4 Jahren (maximale Nachbeobachtungszeit) .…”
Section: Strahlentherapieunclassified
“…berichteten über insgesamt etwa 1300 Tumoren die mittels „Weichstrahltechnik“ (94,9 % klinische Tumorfreiheit bei einer mittleren Nachbeobachtung von 77 Monaten) behandelt wurden . Allerdings ist extreme Vorsicht bei tiefer infiltrierenden Läsionen geboten, da hier besonders die „weichen Röntgenstrahlen“ aufgrund der geringen Eindring‐ und Wirktiefe Nachteile bezüglich der Tumorkontrolle zeigen (bei Tumordicke > 5 mm schon < 90 % physikalische Dosis bei einer Energie von 50 kV und exponentieller Abfall in weiterer Tiefe) . Die Gesamtdosis sollte bei Normofraktionierung (5 × 2 Gy pro Woche) mindestens 60 Gy betragen, bei größeren Läsionen (> 2 cm horizontaler Durchmesser) ist eine Dosiserhöhung bis auf 66 Gy möglich.…”
Section: Strahlentherapieunclassified
See 1 more Smart Citation